ANALYSIS OF STRAIN AND DEFLECTION IN CONCRETE WITH ZEOLITE AS CEMENT SUBSTITUTION USING DIC METHOD - Sofiyah sofi; Trias Rahardianto; Bobby Asukmajaya Raharjo (Jurusan Teknik Sipil Politeknik Negeri Malang, 2025)
Concrete is one of the most chosen materials in the construction world due to its exceptional properties, such as high compressive strength, fire resistance, and weather resistance. One natural material that can be used as an additive or substitute in concrete to improve, maintain, or even enhance the existing strength of concrete mixtures is zeolite. Adding zeolite to the mixture is expected to minimize strain and deflection compared to the normal concrete. The examination of the mechanical properties of concrete material is crucial to ensure that the material can be used. Several existing concrete material testing methods and equipments require relatively high investment costs. The application of the Digital Image Correlation (DIC) method offers a comprehensive alternative that can replace the expensive traditional strain gauge. This method uses a digital camera and Zeiss Inspect Correlate software. This study aims to determine the effect of zeolite application in concrete as a cement substitute on concrete strain and deflection implementing the DIC method. The results showed that concrete with zeolite substitution has a compressive strength of 25.02 MPa and a flexural strength of 4.13 MPa, which are lower than the compressive and flexural strengths of concrete without zeolite substitution, which are 29.10 MPa and 6.88 MPa, respectively. Additionally, the strain and deflection values obtained from concrete with zeolite substitution are 0.0042 and 1.690 mm, respectively, which are higher than the strain and deflection of concrete without substitution, which are 0.0033 and 1.253 mm, respectively. Therefore, it can be concluded that the addition of zeolite as a cement substitute cannot minimize strain and deflection in concrete and the results of the analysis using the DIC method show a high level of accuracy, proven to be significantly correlated with the measurement results of the instruments.